Psychological factors associated with failure of detoxification treatment in chronic headache associated with medication overuse. (December 2016) - Bottiroli, S; Viana, M; Sances, G; Ghiotto, N; Guaschino, E; Galli, F; Vegni, E; Pazzi, S; Nappi, G; Tassorelli, C
Aim: The aim of this study was to evaluate the psychological factors associated with a negative outcome following detoxification in a 2-month follow-up in medication-overuse headache. Methods: All consecutive patients entering the detoxification program were analysed in a prospective, non-randomised fashion. Psychiatric conditions and personality characteristics were assessed using the Structured Clinical Interview for DSM-IV Disorders (SCID-I) and the Minnesota Multiphasic Personality Inventory (MMPI)-2. χ 2 tests, one-way analyses of variance, and odds ratios (ORs) were used. Results: A total of 248 patients completed the follow-up: 156 stopped overuse and their headaches reverted to an episodic pattern (Group A); 23 kept overusing without any benefit on headache frequency (Group B); and 51 stopped overuse without any benefit on headache frequency (Group C). The prognostic factors for the outcome of Group B were higher scores on the correction (OR 1.128; p  = 0.036), depression (OR 1.071; p  = 0.05), hysteria (OR 1.106; p  = 0.023), and overcontrolled hostility (OR 1.182; p  = 0.04) MMPI-2 scales, whereas those for Group C were psychiatric comorbidities (OR 1.502; p  = 0.021) and higher scores on the hysteria scale (OR 1.125; p  = 0.004). Conclusions: The outcome of detoxification is influenced by psychological factors that should be considered when considering treatment strategies.